Research on color coding of fighter jet head-up display key information elements in air–sea flight environment based on eye-tracking technology. (August 2022) - Niu, Yafeng; Zhou, Tianyu; Bai, Ling
HUD is currently the main flight status display commonly used in modern fighter jets. Color coding is an important method in HUD visual information display. Different weather, terrain, climate, time, season, and other environmental phenomena will affect the HUD. The HUD's multi-color display mode has become a key method to solve the overload display of dynamic and static information in complex flight environments. This paper discusses the use of eye-tracking equipment to record eye movement experimental data using different HUD color schemes, as well as the correct rate and response time to complete the task, in order to evaluate the color combinations of different characters in different high-altitude and sea flight background conditions. Cognitive status was obtained by seven key eye movement indicators (average fixation time, first fixation duration, fixation ratio, fixation time ratio, fixation track length and lookback times, and pupil diameter) designed by color-coded dimensions to evaluate the key element information of the HUD: discernibility, which is related to average fixation time, duration of first fixation, and pupil diameter; perceptibility, which is related to gaze ratio, fixation time ratio, and other indicators; and accessibility, which is related to fixation track length and number of lookbacks. At the same time, the background color brightness interval that affects color matching was obtained, and five key information colors (K1(0, 100, 100), K2(30, 100, 100), K3(300, 100, 100), K4(330, 100, 100), and K5(60, 100, 100)) were selected for experimental exploration to obtain the best matching scheme for color coding of key elements of the HUD against different lightness backgrounds. The results indicate that against a flight background with ocean brightness, ranges are [1–20], [21–40], [41–60], and [61–99] and colors with hues of 30, 300, 60, and 300 are selected for the key information. Finally, the results give an improvement and optimization plan for the HUD. The research conclusion provides some guidance for HUD design and improvement for different flight backgrounds, and a reference for improving pilots' cognitive performance.